Pengaruh Social Media Overload terhadap Produktivitas Belajar Mahasiswa - Shandra Elvyra Sudarsono Putri; Aryo Pinandito; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Social media users in Indonesia are increasing every year. The ease of use of social media provides many benefits to users, especially college students. Social media is used by students as a means of sharing and exchanging learning-related materials, seeking academic information, and interacting with friends and family. Students are still not fully aware of the factors that can trigger the negative impacts of using social media. This study aims to determine the influence of social media overload factors on student learning productivity using linear regression analysis. The research data collection technique used a questionnaire that obtained the data from as many as 100 respondents. Based on the results of the data analysis, only communication overload affects student learning productivity. Communication overload shows a very weak correlation to learning productivity. The test result was 18%, so 82% is explained by other variables outside the model used.